The pedagogical support for early professional self-determination of schoolchildren - Kudysheva, Ainash; Popandopulo, Anar; Xembayeva, Saule; Chsherbakova, Yelena; Khaimuldina, Anara; Pshembayeva, Elmira (Institute of Advanced Engineering and Science, 2025)
In a rapidly changing world, early professional self-determination becomes critically important for young people. The aim of this study is to evaluate a model of psychological and pedagogical support designed to assist schoolchildren in making informed career decisions at early stages of education. The problem lies in the lack of effective support systems within educational institutions, leading to a mismatch between graduates’ career choices and their actual professions. The proposed solution is a comprehensive model that integrates psychological, pedagogical, and methodological support, tailored to individual needs. The study involved 180 children from three schools, divided into control and experimental groups. The experimental group underwent a structured educational program that included self-assessment, exploration of career opportunities, goal setting, and enhancement of self-efficacy and motivation. Pre- and post-tests with developed scales were used to assess career clarity, self-efficacy, and motivation. The results showed that the support model significantly improved career clarity, self-efficacy, and motivation in the experimental group compared to the control group. Key improvements were observed in self-understanding, exploration of career opportunities, and goal setting. Thus, the developed model can aid in early professional self-determination, offering a valuable tool for educators and policymakers. Its implementation can better support students in their career choices, fostering their personal and professional growth.